The challenges of social participation in Santiago de Cuba (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
In a society where social participation has been an essential component of the progress achieved, there are symptoms of exhaustion and limitations in its potential. The incorporation of new measures in the current context has not been able to give the required impetus. A set of limitations can be observed, the solution of which is a commitment of the authorities and local communities that join efforts to face the challenges posed. The article focuses on the argumentation of the challenges supported by research that provides the elements of judgment that support the discourse. The times demand the experimentation of new behaviors and attitudes.